Differential Staining for Conjunctival Impression Cytology - Perera, S.C.; Cullen, A.P. (Canadian Journal of Optometry, 2026)
Conjunctival disease or trauma results in variability in cell type and numbers as determined by impression cytology. Differenntial staining is effective in facilitating identification of specific cell changes. Differential staining on conjunctival impressions revealed surface epithelial changes and the presence of eosinophils following exposure to ultraviolet B.